DEVELOPMENT OF CIVIL LAW THROUGH EMPOWERING JURISPRUDENCE: A COMPARATIVE STUDY OF CIVIL LAW AND COMMON LAW SYSTEMS - Pinem, Faisal Hadi; Kamello, Tan; Purba, Hasim; Ikhsan, Edy (NOMOI Law Review, 2024)
The development of civil law in resolving disputes needs to be addressed by implementing court decisions that have permanent legal force in the form of jurisprudence. Civil law problems that are developing rapidly are unable to be followed by existing legal regulations, and are not even sufficient to answer all the problems in civil law itself. The research uses a normative juridical research type. Jurisprudence has a big role and contribution in the development of civil law to fill legal gaps and provide legal certainty. Article 10 Paragraph (1) Law no. 48 of 2009 states that